Embeddedness as a Process - Chajewski, Leszek (Conference Papers -- American Sociological Association, 2005)
This article describes a strategy of modeling embeddedness of economic behavior as a process, as opposed to viewing it as a time-independent relationship between behavior and a social factor in which it is subsumed. I first reconstruct Polanyi's classic processual model of embeddedness and derive from it a set of intuitive tests, which are then applied to key modern approaches in economic sociology: structural, neo-institutional, neo-weberian and Fligstein's embeddedness-as-identity-formation approach. Finally, I describe main analytic and empirical consequences of the processual approach to embeddedness. Key among these consequences is that not all forms of embeddedness are of equal significance, therefore, economic sociology's empirical focus should shift from demonstrating that behavior is more likely to be embedded than not, to the forms of economic behavior that are likely to dominate alternative types of behavior.
Keywords: cultural and neo-weberian perspectives in economic sociology; economic sectors; economic systems; embeddedness; embeddedness and identity formation; embeddedness process; empirical research; forms of economic integration; market transitions; neo-institutionalism; new economic sociology; social factors; social status; socioeconomics

"Economic Life, Institutions, and Social Action: Reflections on Polanyi's Approach to Studying Economic Life" - Gemici, Kurtulus (Conference Papers -- American Sociological Association, 2005)
The article focuses on the relevance of economist Karl Polyani's economic theories and tries to analyze if his book titled "The Great Transformation," could be considered as the foundation of current economic sociology and international political economy. The author of the article says that Polayni's theories focuses on contemporary economic sociology, market economy's self-destructive approach and consideration of the market economy as integral part of the society. His work on institutedness and economy's embedness in society are working as base for most of the challenging theories in economic sociology.
Keywords: Great Transformation, The (Book); capitalism; economic behavior; economics; embeddedness; institutions; methodology; socioeconomics

What Can Marxists Learn From Polanyi? - Özel, Hüseyin; Yılmaz, Erdal (10th International Polanyi Conference: “Protecting Society and Nature from Commodity Fiction”, October 13-16, 2005, 2005)
The starting point of this paper is this comment by Rhoda Halperin on the relationship between Marx and Polanyi. Our objective is, however, to examine how reading of Polanyi could be useful to understand, or supplement, Marx’s own views on both capitalism and the “human condition” in general, rather than vice versa. In this regard, we argue first that those followers of Polanyi who believe that Marx should be treated as a rival of Polanyi, and that Marx’s “historical materialism” and his critique of capitalism is economically (or technologically) determinist, mechanistic, and reductionist, either misunderstand or misrepresent Marx.. We believe that these properties should be taken as representing the position that could be called as “vulgar” Marxism, rather than representing Marx’s own position. This type of “vulgar” Marxism is first of all positivistic or scientistic in its outlook; that is, it maintains the positivistic distinction between facts and values and thus considers ethics as being trivial in understanding and resisting capitalism. Secondly, its “materialistic conception of history” is guilty of the “economistic fallacy”, since it overlooks the fact only under capitalism do we have an “economic society”. Third, its class conception is mechanistic and reductionistic in that every act of resistance to capitalism must be explained in terms of, and carried out through, class struggle. Last, but not least, the “vulgar” Marxism is fatalistic in the sense that it maintains the view that capitalism will inevitably be collapsed through class struggle. We believe that none of these charges can be sustained if one considers Marx’s work in its entirety, and that there are important affinities and overlaps between Marx and Polanyi.
Keywords: MARX, Karl, 1818-1883; critique of capitalism; fictitious commodities; substantiveness